Pertumbuhan in vitro stek mikro singkong (Manihot esculenta Crantz.) - Ardian Ardian (Jurnal Penelitian Pertanian Terapan, 2010)
Propagation of cassava through in vitro culture is needed by farmers and agro industries to fulfill the need of the best and the newest clone as soon as after that clone is released by government. The objective of this research is to know the effect of the application of some concentration sucrose and activated charcoal on in vitro and ex vitro growth of micro-cutting of cassava. Explants used were one-node cuttings of cassava, which were derived from sterile shoot culture. The explants were cultured on MS basal medium supplemented with 0,2 mg.l-1 benzyl adenine. This research was arranged in completely randomized design with the treatments consisting of some concentrations of sucrose: 3%, 4% and 5% and concentration of activated charcoal: 0% and 0,1%. Each treatment was replicated 7 times with 4 explants in each experiment unit. The best growth micro-cutting of cassava in vitrowas achieved by treatment of 3% sucrose without activated charcoal. Keywords: Micro-cutting, Cassava